Exploring theory-based behavioral interventions promoting COVID-19 prevention and healthcare-seeking for migrant worker men in Singapore: a qualitative study - Zoe Jane-Lara Hildon; Chitra Panchapakesan; Md Tahmid Hasan; Nazrana Khaled; Alyssa Yenyi Chan; Shilpi Tripathi; Melvyn Chung Pheng Wong; May O. Lwin; Mark Chen I-Cheng; Kaosar Afsana (BMC, 2022)
Abstract Background The first wave of COVID-19 during April to July 2020 in Singapore largely affected the migrant workers living in residential dormitories. A government taskforce working with dormitory operators, employers and non-government agencies came together to deliver behavioral interventions and health care services for migrant worker as dorms were imposed movement restrictions. To fill the research gap in understanding movement restriction experiences of migrant workers, this research seeks to describe dormitory contexts and explore behavior change related to both prevention of transmission as well as healthcare seeking for COVID-19 among male migrant workers. Methods With social constructivism as the foundation for this study, 23 telephone interviews were conducted with Bangladeshi and Indian migrant workers. A theory-informed, data-driven conceptual framework, characterized by the "Four Ss": Sensitization, Surveillance, Self-preservation, and Segregation was first generated and later used to frame second-stage, more in-depth, thematic analyses. An effective multipronged approach was documented, persuading migrant workers in our case-study to improve hygiene and follow some safe distancing measures, and adhere to help-seeking when symptomatic. Results Rapid collective adaptation was demonstrated; it was propped up by effective harnessing of infrastructure and technology. While technology and digital platforms were central to shaping Sensitization for prevention-related behaviors, interpersonal communication, especially peer-sharing, was key to normalizing and accepting healthcare delivery and norms about healthcare seeking. Interpersonal factors particularly supported successful implementation of case-detection Surveillance, stimulating Self-preserving and acceptance of rules, and was found helpful to those Segregated in recovery facilities. In contrast, encouraging prevention-related behaviors relied more heavily on multiple online-platforms, phone-based e-learning/knowledge testing, e-monitoring of behavior, as well as interpersonal exchanges. Conclusion Overall, the findings showed that the conception of the Four Ss helped inform intervention strategies. Anchoring these towards optimal use of technology and harnessing of interpersonal communication for prevention and promotion of healthcare seeking in the planning of future Infectious Disease outbreaks in closed institutional settings is recommended.